2020
DOI: 10.1088/1755-1315/458/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bactrocera spp. on some mango varieties at Kecamatan Talun, Kabupaten Cirebon

Abstract: Fruit fly (Bactrocera spp.) is a major pest of horticultural crops, especially fruits. Fruit fly larvae feed on the flesh of fruit, and cause the decrease of both quantity and quality of the production. Fruit fly species on certain fruit in an area is important to be identified to make a right decision in choosing the control methods. The objectives of this study were to identify the fruit fly species, and determine the dominant species and diversity index of fruit flies on mangoes Gedong Gincu, Cengkir, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…The identification of fruit flies at the research site proved that three species attacked mango varieties were B. dorsalis, B. carambolae, and the interspecific hybrids of B. carambolae and B. dorsalis (Figure 3). This result was in agree with the research findings of [12], that B. dorsalis, B. carambolae, and interspecific hybrids of B. carambolae and B. dorsalis, were found in Arumanis, Cengkir, and Gedong Gincu mangoes plantation at Cirebon Regency, West Java. Fruit flies B. dorsalis and B. carambolae have close kinship, making they are quite difficult to distinguish the morphology of the two species directly without using tools because they look almost similar [20] between B. dorsalis (Figure 3a) and B. carambolae (Figure 3b).…”
Section: Fruit Fly Identificationsupporting
confidence: 93%
See 1 more Smart Citation
“…The identification of fruit flies at the research site proved that three species attacked mango varieties were B. dorsalis, B. carambolae, and the interspecific hybrids of B. carambolae and B. dorsalis (Figure 3). This result was in agree with the research findings of [12], that B. dorsalis, B. carambolae, and interspecific hybrids of B. carambolae and B. dorsalis, were found in Arumanis, Cengkir, and Gedong Gincu mangoes plantation at Cirebon Regency, West Java. Fruit flies B. dorsalis and B. carambolae have close kinship, making they are quite difficult to distinguish the morphology of the two species directly without using tools because they look almost similar [20] between B. dorsalis (Figure 3a) and B. carambolae (Figure 3b).…”
Section: Fruit Fly Identificationsupporting
confidence: 93%
“…The study aligns with [11], which shows the highest percentage of fruit fly B. dorsalis at 93% and B. carambolae at 7%. Research by [12] reported that in Talun District, Cirebon Regency, West Java, Indonesia, fruit fly attacked Gedong Gincu mango, Cengkir mango, and Arumanis mango were found…”
Section: Introductionmentioning
confidence: 99%
“…It was carried out once a week, five times. Based on Susanto et al (2020), 10% of all fruit flies that were trapped at the experimental site were taken randomly for identification based on their morphological characters in the laboratory using a z61 typed microscope. In addition, observations on biotic data, which was the host availability factor, and abiotic data, such as rainfall and rainy days, were also carried out.…”
Section: Observation Of the Number Of Fruit Fliesmentioning
confidence: 99%
“…Pujiastuti et al (2009) melaporkan B. carambolae dan B. papayae menyerang buah-buah belimbing, mangga, dan pepaya di Sumatera Selatan. Hasil lebih lengkap dilaporkan oleh Susanto et al (2020)…”
Section: Pembahasanunclassified